Characterization of Sensorineural Hearing Loss in Adult Patients With Sickle Cell Disease: A Systematic Review and Meta-analysis. Issue 1 (January 2021) - Kapoor, Elina; Strum, David; Shim, Timothy; Kim, Sunny; Sabetrasekh, Parisa; Monfared, Ashkan
Abstract : Objectives and Main Outcome Measures: To determine the prevalence of sensorineural hearing loss (SNHL) attributable to sickle cell disease (SCD) in the global adult population and to identify factors contributing to its severity. Study Design: Systematic Review and Meta-analysis. Methods: We performed a comprehensive literature search for scientific articles in PubMed, Scopus, CINAHL, Web of Science, and the Cochrane Library that reported the incidence of hearing loss in populations over 18 years of age with SCD. Results: We identified 138 studies from the initial search, 12 of which met inclusion criteria and were utilized for data analysis. A total of 636 SCD patients and 360 controls were included in the Cochrane Review Manager 5.3 meta-analysis. There was a statistically significant increase in the prevalence of SNHL in adults with SCD compared with the general population with a cumulative risk ratio (RR) of 6.03. Conclusions: This is the first systematic investigation of the relationship between SCD and SNHL in adult patients across the globe. SNHL is more prevalent in patients with SCD, specifically those of the HbSS genotype, than the general population likely due to the pathophysiology of the disease and its effects on labyrinthine microvasculature. The increased prevalence of SNHL in the adult SCD population warrants future research into the predictors of SNHL severity and merits routine audiometric monitoring of adult SCD patients.